Design and Implementation of DC to DC Converter for Mobile Phone Charging Based on Microcontroller - Athian Ali Muhammad; Ekki Kurniawan; Budi Setiadi; Ferryn Marchellyn (SAINSTEK, 2025)
The increasing demand for portable and energy-efficient electronic devices has driven innovation in smartphone charging technology. Continuous smartphone operation requires an efficient power source, especially when AC power is unavailable. This study presents the design and implementation of a microcontroller-based DC-to-DC Buck Converter for smartphone charging using a 12V DC input. The system employs a MOSFET as a switching device controlled by PWM signals generated by an ATMega16 microcontroller. By adjusting the PWM duty cycle, the microcontroller regulates the output voltage to meet different smartphone charging requirements.The converter steps down the 12V DC input to a lower, stable voltage suitable for mobile phone charging while maintaining high efficiency. Essential circuit components, including the microcontroller, MOSFET, inductor, and capacitor, are arranged to ensure smooth voltage conversion with minimal ripple. Experimental results confirm that the designed converter effectively produces adjustable voltage levels compatible with various smartphones.Overall, this system demonstrates a reliable and energy-efficient solution for DC-powered smartphone charging, offering flexibility for use in portable and off-grid conditions.